Towards the definition of the concept «water and greenery framework» - Gushchin Alexander N.; Divakova Marina N. (Архитектон)
Currently, there is a surge of interest in water and greenery frameworks. Further development of architectural landscaping practice requires a precisely formulated conceptual apparatus. In defining the concept of "water and greenery framework", we are based on formal logic and use a generic to specific method of concept definition. Possible alternatives for choosing a generic concept are discussed. The water and greenery framework is considered as a component of the cultural landscape. Further, we consider the general features that the water greenery framework inherits from the generic concept and individual (specific) features that distinguish the water and greenery framework.